2016
DOI: 10.1002/maco.201608831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas flow rate on oxidation behaviour of alloy 625 in wet air in the temperature range 900–1000 °C

Abstract: In many industrial processes, the flow rate of hot gaseous service environments may be in the range of several m/s. In the present paper, the effect of gas flow rate on the high temperature oxidation behaviour of alloy 625 in wet air is presented. The gas velocity was varied from near static conditions to linear gas flow rates up to 6 m/s. The oxidation kinetics were studied by gravimetry during cyclic/discontinuous testing at 900 and 1000 °C. The oxide scales and the subsurface depletion zones formed during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…Similar results were received from Pint and Young who observed a proper accordance of calculated and experimental data at low flow rates of approximately 17 mm/s using Equation . This is in marked contrast to Huczkowski et al, in which they argue that Equation is not applicable for low flow rates due to the interference of the boundary layers.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Similar results were received from Pint and Young who observed a proper accordance of calculated and experimental data at low flow rates of approximately 17 mm/s using Equation . This is in marked contrast to Huczkowski et al, in which they argue that Equation is not applicable for low flow rates due to the interference of the boundary layers.…”
Section: Discussioncontrasting
confidence: 61%
“…The derivation of the formula is accurately described . Huczkowski et al demonstrated the limitations of Equation . Especially the width of the boundary layer along the specimen is frequently similar to the diameter of the reaction tube at low flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…While many investigations [15][16][17][18] have been carried out on the oxidation behaviour of conventional Inconel 625 in air, there has been less work on the high-temperature reactivity of the 3D manufactured Inconel 625 [19].…”
Section: Introductionmentioning
confidence: 99%
“…At high pressure, O 2 additions have shown slightly negative effects or little effect . It has been suggested that combinations of H 2 O and O 2 at high pressure could react with Cr‐rich reaction products to form volatile Cr oxy‐hydroxides thereby accelerating the degradation rate (ie, rate of Cr loss) of both Fe‐ and Ni‐base alloys . This degradation would be particularly important for thin‐walled structures in heat exchangers.…”
Section: Introductionmentioning
confidence: 99%